POPULAR EXTENSION: HISTORICAL MILESTONES: POPULAR EXTENSION: HISTORICAL MILESTONES - Soares de Araújo, Renan (2021)
The Extension has historically stood out as the academic pillar through which various social practices have been carried out. In this context, we witness the existence of an extension perspective oriented based on the Freirian concept of Popular Education. In view of the above, the present manuscript aimed to outline, from a historical diachronic approach, the process of constituting the Extension field in Popular Education, in the Brazilian context. For this, a descriptive bibliographic search was used, with a qualitative approach, based on the narrative review. It is observed that, at first, these Popular Education Extension initiatives were developed in a way unrelated to the university as a institution. With the beginning of the military dictatorship period, in 1964, these practices began to be severely repressed, even so, they continued to occur again. With the end of the military regime in 1985 and political openness, these practices started to be recognized institutionally. In a row, with the consolidation of some government policies, these experiences were enjoying institutional credibility and gaining more and more prominence and recognition. Although it is not a hegemonic practice, it has gradually been conquering space in the multifaceted university scenario and consolidating itself as a possibility.